Penerapan PJBL “ Klipop” Pendidikan Pancasila untuk Meningkatkan Hasil Belajar Kelas 5 UPT SDN Kutorejo 1 - Nofa Andika Ahmad Yasin; Nur Afifah; Sukisno Sukisno; Dwi Retmawati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to analyze the implementation of project-based learning through the creation of clipping envelope(KLIPOP) of norms in the Pancasila Education subject, as well as to evaluate its impact on improving the learning outcomes of fifth-grade students at SDN Kutorejo 1 Tuban. The background of this research is the low student achievement in Pancasila Education, often caused by conventional, theoretical teaching methods that lack connection to students’ real-life experiences. The research method used is Classroom Action Research (CAR) with a descriptive quantitative approach. Data were collected through observation, interviews, documentation, and the results of pre-tests and post-tests. The findings show that project-based learning is effective in improving students’ learning outcomes. This is evidenced by the increase in the average test score from 74.8 (pre-test) to 91.3 (post-test). Students also demonstrated greater engagement, creativity, and collaboration in understanding the norms contained in Pancasila. By involving students in contextual activities, such as collecting information and creatively designing norm envelopes, learning becomes more meaningful and applicable. Therefore, this learning model can serve as a strategic alternative to enhance students’ understanding and academic performance in Pancasila Education at the elementary level.